Analytic Hierarchy Process: Strategi Peningkatan Kinerja UMKM Batik di Kabupaten Bojonegoro - Silvi Ananda Putri; Retno Muslinawati; Joko Hadi Susilo (Universitas Batanghari Jambi, 2023)
The research aims to determine the priority strategies for improving performance, Financial Literacy, Human Capital, and Marketing for Batik Bojonegoro Micro, Small and Medium Enterprises (MSMEs). This study used the Analytic Hierarchy Process (AHP) approach with a population of 56 Batik SMEs in Bojonegoro Regency. There are 8 research samples taken by purposive sampling technique. It is hoped that this research can determine the most important parties that influence the MSME performance improvement strategy through the AHP approach. Based on the results of AHP calculations, it is known that the policy priority strategy on sub-criteria to be considered in an effort to improve the performance of batik MSMEs is that MSME actors need to increase experience, knowledge, and education so that they can improve the performance of Batik MSMEs.